2011
DOI: 10.5402/2011/895082
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Nurses' Observation Scale for Cognitive Abilities (NOSCA)

Abstract: Background. To assess a patient's cognitive functioning is an important issue because nurses tailor their nursing interventions to the patient's cognitive abilities. Although some observation scales exist concerning one or more cognitive domains, so far, no scale has been available which assesses cognitive functioning in a comprehensive way. Objectives. To develop an observation scale with an accepted level of content validity and which assesses elderly patients' cognitive functioning in a comprehensive way. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The level of consensus within the Delphi panel that is considered acceptable by the research team also differs, with some studies reporting an agreement level set at 90% (Pfleger, McHattie, Diack, McCaig, & Stewart, 2008) and others setting the agreement level at 70% (Persoon, Banningh, van de Vrie, Rikkert, & van Achterberg, 2011).…”
Section: Level Of Consensusmentioning
confidence: 99%
“…The level of consensus within the Delphi panel that is considered acceptable by the research team also differs, with some studies reporting an agreement level set at 90% (Pfleger, McHattie, Diack, McCaig, & Stewart, 2008) and others setting the agreement level at 70% (Persoon, Banningh, van de Vrie, Rikkert, & van Achterberg, 2011).…”
Section: Level Of Consensusmentioning
confidence: 99%
“…Intervention effectiveness refers to the clinical improvement of the service users as a result of Cognitive Adaptation Training. The effectiveness of Cognitive Adaptation Training was determined by the improvements of the service users on daily functioning and cognitive functioning measured by 2 observational questionnaires: Life Skills Profile [ 34 ] and the Nurses’ Observation Scale of Cognitive [ 35 ]. The Life Skills Profile consists of 39 questions on a 4-point scale (total score range: 39-156) and measures various aspects related to daily life activities: self-care; nonturbulence; social contact; communication; and responsibility.…”
Section: Methodsmentioning
confidence: 99%
“…Results on the Life Skills Profile from the previous research [ 7 ] evaluating the effectiveness of Cognitive Adaptation Training revealed a significant effect for people receiving Cognitive Adaptation Training in addition to treatment as usual compared to treatment as usual only. The Nurses’ Observation Scale of Cognitive Abilities [ 35 ] measures cognitive functioning and includes 39 items (total score range: 0-121) subdivided into 8 cognitive domains (subscales): attention, perception, memory, orientation, higher cognitive domains, thoughts, language, and praxis. The Nurses’ Observation Scale of Cognitive Abilities is scored on a 4-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 In addition, self-reported questionnaires and monodisciplinary observation tools incorporating ICF domains were developed. [9][10][11][12] However, self-reported questionnaires strongly depend on preserved cognitive abilities (i.e. insight) of patients and monodisciplinary observation tools do not reflect the whole condition of a stroke patient within a multidisciplinary rehabilitation setting.…”
Section: Lucerne Icf-based Multidisciplinary Observation Scalementioning
confidence: 99%